Imitations of Insanity and Victorian Medical Aesthetics - Logan, Peter (Romanticism and Victorianism on the Net, 2008)
AbstractThe pre-eminent figure in mid-Victorian psychological medicine, Dr. John Conolly had his reputation damaged in the 1850s by scandals linking him to cases of wrongful confinement, including one that figures in Charles Reade’s novel, Hard Cash. This essay looks at two major works Conolly published during the scandals and argues that they are responses to the charges against him. Both works focus on representations of insanity in art, rather than actual patients. “The Physiognomy of Insanity” (1858-59) is a series of essays on photographic portraits of asylum patients, and his essays prove to be more fictional than factual. A Study of Hamlet (1863) looks at the ambiguity of madness in Shakespeare’s portrayal of Hamlet, but it explains how Conolly understood the relationship between fact and fiction in cases of insanity. In both works, Conolly defends himself as an aesthete and defines his diagnostic method as a deliberate and necessary form of impressionism.